Evaluasi Kinerja Birokrasi Dinas Pendidikan Kabupaten Purwakarta dalam Peningkatan Mutu Layanan Pendidikan Era Otonomi Daerah - Sadiyah; Deasy Nurmaulidah; Nurlaeni; Deding Ishak; Helmawati; Wahyu Satya Gumelar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Improving the quality of educational services has become a major challenge for local governments in the era of regional autonomy, particularly regarding the effectiveness of bureaucratic performance. This study aims to analyze the performance of the Education Office bureaucracy in Purwakarta Regency in supporting the improvement of educational service quality. The research employed a qualitative descriptive approach, with data collected through in-depth interviews, participatory observation, and document review. Research informants included structural officials, staff of the Education Office, and educational service users at the school level, selected using purposive sampling. The results indicate that the Education Office bureaucracy has implemented programs to improve service quality through procedural simplification, policy adjustments according to local needs, and coordination with educational units. However, challenges were identified, including limited human resource capacity, suboptimal internal coordination, disparities in service responsiveness across regions, and irregular outcome-based performance evaluation. The study concludes that strengthening the performance management system, enhancing human resource capacity, and improving cross-unit coordination mechanisms are crucial factors in enhancing bureaucratic effectiveness and service quality. These findings provide a basis for developing strategies to create a more responsive and sustainable educational bureaucracy. Keywords: Bureaucratic performance, Education Office, quality of educational services, regional autonomy, performance evaluation